Cultivo do sorgo usando água de esgoto doméstico tratado como fonte hídrica - Lira, Raniere Barbosa de (Universidade Federal Rural do Semi-Árido, 2016)
The use of treated sewage effluents is a way of avoids environmental pollution and also a viable choice to increase water availability in arid and semiarid regions. However, it is necessary to understand characteristics of the end product to avoid undesirable effects and, to allow its use as material for irrigation and plant fertilization, among others. As option to agricultural produce, sorghum plants were growth in open-field under irrigation with treated domestic wastewater from wastewater treatment plant located in Milagres Settlement Project, Apodi state, Brazil. The experiment was carried out using the experimental design in completely randomized blocks, with three replications. Treatments followed a factorial scheme 3 x 3, with three water source (well water - control, treated sewage effluent and, mixture of 50% water well + 50% treated sewage effluent) and, three sorghum cultivars (IPA 2502, BRS 506 and BRS Ponta Negra). Result showed that BRS Ponta Negra cultivar responded positively to the increase of wastewater in relationship the variables leaf area, leaf number, dry matter and green mass weight, than the other treatments. Agricultural use of treated domestic wastewater and mixtures of 50% well water + 50% treated domestic wastewater were water sources that resulted in higher sorghum yields. The vegetative and productive increase of sorghum plants BRS 506, IPA 2502 and Ponta Negra was positively influenced by the waters: sewage, mixture and supply successively used in the fertirrigation and the waters sewage and mixture, resulted in greater production of biomass: briquettes production, Production of ethanol and calorific value
Cultivation of sorghum using domestic sewage treated as a water source
Keywords: Reuso de água; Recursos hídricos; Fonte de nutrientes; Agricultura; Water reuse; Water resources; Nutrient source; Agriculture; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO